Management of Cancer Cachexia: ASCO Guideline - Roeland, Eric J; Bohlke, Kari; Baracos, Vickie E; Bruera, Eduardo; Del Fabbro, Egidio; Dixon, Suzanne; Fallon, Marie; Herrstedt, Jørn; Lau, Harold; Platek, Mary; Rugo, Hope S; Schnipper, Hester H; et al. (Journal of clinical oncology, 2020)
To provide evidence-based guidance on the clinical management of cancer cachexia in adult patients with advanced cancer. A systematic review of the literature collected evidence regarding nutritional, pharmacologic, and other interventions, such as exercise, for cancer cachexia. PubMed and the Cochrane Library were searched for randomized controlled trials (RCTs) and systematic reviews of RCTs published from 1966 through October 17, 2019. ASCO convened an Expert Panel to review the evidence and formulate recommendations. The review included 20 systematic reviews and 13 additional RCTs. Dietary counseling, with or without oral nutritional supplements, was reported to increase body weight in some trials, but evidence remains limited. Pharmacologic interventions associated with improvements in appetite and/or body weight include progesterone analogs and corticosteroids. The other evaluated interventions either had no benefit or insufficient evidence of benefit to draw conclusions on efficacy. Limitations of the evidence include high drop-out rates, consistent with advanced cancer, as well as variability across studies in outcomes of interest and methods for outcome assessment. Dietary counseling may be offered with the goals of providing patients and caregivers with advice for the management of cachexia. Enteral feeding tubes and parenteral nutrition should not be used routinely. In the absence of more robust evidence, no specific pharmacological intervention can be recommended as the standard of care; therefore, clinicians may choose not to prescribe medications specifically for the treatment of cancer cachexia. Nonetheless, when it is decided to trial a drug to improve appetite and/or improve weight gain, currently available pharmacologic interventions that may be used include progesterone analogs and short-term (weeks) corticosteroids.